Waist circumference, body mass index, and skinfold thickness as potential risk factors for high blood pressure in adolescents - Roslina Dewi; rafita ramayati; Nelly Rosdiana; Oke Rina Ramayani; Rosmayanti Siregar; Beatrix Siregar (Indonesian Pediatric Society, 2019)
Background The prevalence of hypertension in children and adolescents has increased with the rising obesity epidemic. Recent studies have found that prevalence of hypertension was higher in obese children or adolescents than in the normal weight ones. Anthropometric measurements such as body mass index (BMI), waist circumference, and skinfold thickness have been used as criteria to determine obesity in children and adolescents. Increased waist circumference has been most closely related to increased blood pressure. Objective To compare waist circumference, BMI, and skinfold thickness as potential risk factors for hypertension in adolescents. Methods This cross-sectional study was conducted in May 2014 in three senior high schools in Medan, North Sumatera, and included 253 students with normal urinalysis test. All subjects underwent blood pressure, waist circumference, tricep- and subscapular-skinfold thickness (TST and SST), body weight, and body height measurements. The study population was categorized into underweight, normoweight, overweight, and obese, according to four different criteria: waist circumference, BMI, TST, and SST; all variables were analyzed for possible correlations with systolic and diastolic blood pressure. Results There were significant positive correlations between systolic blood pressure and waist circumference (OR 7.933; 95%CI 2.20 to 28.65; P=0.011) as well as BMI (OR 4.137; 95%CI 1.16 to 14.75; P=0.041). There were also significant correlations between diastolic blood pressure and waist circumference (OR 3.17; 95%CI 1.83 to 5.51; P=0.002), BMI (P=0.0001; OR=3.69), TST (OR 4.73; 95%CI 2.31 to 9.69; P=0.0001), and SST (OR 3.74; 95%CI 2.35 to 5.94; P=0.0001). Multivariate analysis showed that waist circumference was a predictive factor for systolic blood pressure (OR 9.667), but not for diastolic blood pressure. Conclusion Waist circumference is the strongest, significant, predictive factor for elevated systolic blood pressure; meanwhile BMI, SST, and TST could be predictive factors for elevated diastolic blood pressure.